Asymptomatic Rare Rib Anomalies: Bifid Rib and Rib Fusion - Ozyurtkan, Mehmet Oguzhan (Derman Medical Publ, 2010)
A variety of normal variants or pathologic conditions of the ribs are overlooked at chest radiography if they are not evaluated carefully. There are various types of congenital anomalies and deformities of the ribs, including developmental fusion of two or more ribs, articulation or bridge formation between two ribs, and bifid rib. Three rare asymptomatic cases of bifid ribs and rib fusion have been presented in this case report. These anomalies were detected incidentally, after a chest X-ray taken for other reasons. These numerical and structural rib abnormalities may occur in isolation or with other congenital anomalies. Radiologists and clinicians dealing with osseous thorax should be familiar with normal variants of the ribs to avoid mistaking them for an abnormality.
Asemptomatik Nadir Kosta Anomalileri: Bifid Kosta ve Kosta Füzyonu
Keywords: Musculoskeletal Abnormalities; Ribs; Thoracic Radiography